REGIONAL LANGUAGE BACKGROUND AND STUDENTS’ COMMUNICATION STYLES IN A MULTICULTURAL CAMPUS CONTEXT - Zuhrianti Hulukati; Hikma Laurestabo; Ariska Damogalad; Muziatun Muziatun (Jurnal Review Pendidikan dan Pengajaran, 2026)
This study aims to analyze the influence of regional language backgrounds on the communication styles of students at Gorontalo State University (UNG), as well as to identify adaptation strategies and potential misunderstandings that occur in intercultural interactions on campus. The approach used in this study is qualitative descriptive with a sociolinguistic perspective. Research data were collected through direct observation and interviews with students from diverse regional language backgrounds, including Gorontalo Malay, Suwawa, Bolaang Mongondow, and Javanese. The results indicate a strong unconscious language transfer, both in word choice (such as the use of affixes like “to” and ‘ndo’ or local terms of address like “ana,” “ngana,” and “kita”) and in vocal intonation. Students from Sulawesi tend to use a firm, high-pitched intonation as a sign of openness, while Javanese students tend to speak more softly to uphold the value of politeness (unggah-ungguh). Differences in interpretation and linguistic norms occasionally lead to cross-cultural misunderstandings. Nevertheless, students successfully minimize conflicts and social distance through communicative accommodation, such as the use of Indonesian, adjustment of speech tone, and direct clarification. This study concludes that the UNG campus environment can function as a small-scale multicultural space, where linguistic diversity does not weaken communication but rather strengthens tolerance among students.